Epigallocatechin 3-gallate inhibits the plasma membrane Ca2+-ATPase: effects on calcium homeostasis - Rinaldi, Debora Eugenia (2021)
Flavonoids are natural compounds responsible for the health benefits of green tea. Some of the flavonoids present in green tea are catechins, among which are: epigallocatechin, epicatechin-3-gallate, epicatechin, catechin and epigallocatechin-3-gallate (EGCG). The latter was found to induce apoptosis, reduce reactive oxygen species, in some conditions though in others it acts as an oxidizing agent, induce cell cycle arrest, and inhibit carcinogenesis. EGCG also was found to be involved in calcium (Ca2+) homeostasis in excitable and in non-excitable cells. In this study, we investigate the effect of catechins on plasma membrane Ca2+-ATPase (PMCA), which is one of the main mechanisms that extrude Ca2+ out of the cell. Our studies comprised experiments on the isolated PMCA and on cells overexpressing the pump. Among catechins that inhibited PMCA activity, the most potent inhibitor was EGCG. EGCG inhibited PMCA activity in a reversible way favoring E1P conformation. EGCG inhibition also occurred in the presence of calmodulin, the main pump activator. Finally, the effect of EGCG on PMCA activity was studied in human embryonic kidney cells (HEK293T) that transiently overexpress hPMCA4. Results show that EGCG inhibited PMCA activity in HEK293T cells, suggesting that the effects observed on isolated PMCA occur in living cells.